The response of high‐impact blocking weather systems to climate change. Issue 13 (12th July 2016) - Kennedy, Daniel; Parker, Tess; Woollings, Tim; Harvey, Benjamin; Shaffrey, Len
Abstract: Midlatitude weather and climate are dominated by the jet streams and associated eastward moving storm systems. Occasionally, however, these are blocked by persistent anticyclonic regimes known as blocking. Climate models generally predict a small decline in blocking frequency under anthropogenic climate change. However, confidence in these predictions is undermined by, among other things, a lack of understanding of the physical mechanisms underlying the change. Here we analyze blocking (mostly in the Euro‐Atlantic sector) in a set of sensitivity experiments to determine the effect of different parts of the surface global warming pattern. We also analyze projected changes in the impacts of blocking such as temperature extremes. The results show that enhanced warming both in the tropics and over the Arctic act to strengthen the projected decline in blocking. The tropical changes are more important for the uncertainty in projected blocking changes, though the Arctic also affects the temperature anomalies during blocking. Key Points: Enhanced warming both in the tropics and over the Arctic act to reduce the frequency of blocking Tropical warming is more important in terms of the uncertainty in projected blocking changes The Arctic also affects the temperature anomalies experienced during blocking